Agroecological approaches to sustainable development - Vikas; Ranjan, Rajiv (Frontiers in Sustainable Food Systems, 2024)
Agroecology has emerged as a fundamental paradigm for developing innovative solutions to major global concerns such as food security, biodiversity loss, and climate change. The core subject of biodiversity conservation emphasizes agroecology's role in the preservation of native species, pollinators, and beneficial creatures through practices such as agroforestry, cover crops, and decreased chemical inputs. Agroecological principles such as polyculture, crop diversity, and integrated pest control help to improve food security by increasing stability and nutrition. Agroecology encourages carbon sequestration, soil health, and greenhouse gas reductions, resulting in climate-resilient farming systems. The literature review revealed that no article thoroughly discusses all of the critical hitting global challenges, such as food security, biodiversity loss, and climate change, in a single study that can be addressed using agroecological principles. This review article attempts to make a connection between numerous challenges that may be solved using agroecological techniques in order facilitate sustainable growth while protecting the environment. The study examines the benefits of incorporating agroecological methodologies into sustainable agriculture, with an emphasis on increasing agroecosystem resilience, improving socioeconomic circumstances for smallholder farmers, rural livelihoods, and local communities, and contributing to climate change mitigation.